Pengembangan Aplikasi Sistem Absensi Kelompok Secara Cepat untuk Pendidikan Tinggi Menggunakan Laravel dan VueJS - Pakpahan, Andrew Fernando (Fakultas Teknologi Informasi - Universitas Advent Indonesia, 2024)
This research presents the development of a Group Attendance System for higher education institutions using Laravel and VueJS frameworks. The system addresses the limitations of traditional attendance tracking methods by offering a web-based, mobile-optimized solution. Employing the Rapid Application Development (RAD) methodology, the study outlines the design and implementation process, including the creation of a user-friendly interface for both administrators and student coordinators. The application facilitates efficient management of student groups, scheduling of meetings, and real-time attendance tracking. Comprehensive blackbox testing validated the system's functionality across critical areas such as user authentication, student registration, and attendance recording. The results demonstrate significant improvements in efficiency, accuracy, and accessibility of attendance management, contributing to the advancement of digital solutions in educational administration..